Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.2355/isijinternational.isijint-2016-418
|View full text |Cite
|
Sign up to set email alerts
|

Development of Rapid Curing Process of Reactive Coke Agglomerate

Abstract: We commercialized Reactive Coke Agglomerate (RCA), a cement-bonded pellet to decrease the thermal reserve zone temperature for the reduction of the reducing agent rate of blast furnaces. To achieve a high productivity of supplying RCA to large blast furnaces, a rapid curing process of RCA using steam was investigated. We obtained rapid curing of RCA within 18 h by combining primary curing for 12 h and stream curing at 80°C for 5 h subsequently with drying for 1 h. This combination provided sufficient strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Both the rate of carbon consumption (RCC) and carbon consumption ratio (CCR) were evaluated using Eqs. (5) and (6). In addition, reduction degree was similarly evaluated using Eq.…”
Section: Softening-melting Testmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the rate of carbon consumption (RCC) and carbon consumption ratio (CCR) were evaluated using Eqs. (5) and (6). In addition, reduction degree was similarly evaluated using Eq.…”
Section: Softening-melting Testmentioning
confidence: 99%
“…The RCC during the tests was evaluated using Eq. (5). The CCR of the agglomerates was evaluated using Eq.…”
Section: Reactivity Testmentioning
confidence: 99%
See 1 more Smart Citation
“…That procedure included 12 hours of primary curing, 5 hours of stream curing at 80°C and 1 hour of drying. 21) On the other hands, Kasai et al demonstrated that the hot briquette procedure without adding any binder also can enhance the strength of green composite. 4,5) However, comparing to the method of pan palletizer to produce the agglomerate, hot briquette procedure seems not only increasing the cost but also decreasing the production rate in the perspective of industrial production.…”
Section: Influence Of C/o On Reduction and Morphologymentioning
confidence: 99%
“…For example, a metal that exhibits a catalytic effect is dispersed in the carbonaceous material to lower the starting temperature of the solution-loss reaction, [2][3][4][5][6][7][8][9][10][11][12][13][14][15] or the carbonaceous material is dispersed or included in the ore agglomerate to accelerate the reduction and gasification reactions. [16][17][18][19][20] These reduce the temperature of the heat reserve zone, which limits the reduction efficiency in the blast furnace, and increase the CO gas utilization rate, so further reduction of the reducing agent ratio is expected. 21,22) In recent years, there are also concerns about an increase in the slag ratio of sinter and the phosphorus concentration in hot metal due to the depletion of high-grade iron deposits.…”
Section: Introductionmentioning
confidence: 99%